Ohmic contact formation and activation for reduced graphene oxide and Sb bilayers contacted CdTe solar cells. (1st November 2020) - Zhu, Linyu; Luo, Guangcan; Yin, Xiaohan; Tan, Bo; Guo, Xuxiang; Li, Wei; Zhang, Jingquan; Wu, Lili; Zeng, Guanggen; Wang, Wenwu
Abstract: Ohmic back contact is one of the keys to fabricate high efficient CdTe solar cells, as it can improve fill factor FF and open-circuit voltage V oc . In this work, antimony-containing reduced graphene oxide (RGO) was prepared and used as a back contact for CdTe thin film solar cells, in which antimony is an effective dopant for CdTe and RGO acts as a hole transport layer and diffusion barrier of antimony in the solar cells. Post deposition annealing was performed to activate the back contact layer and passivate the interface defect states. Electrical performance and apparent quantum efficiency characterization were performed to investigate device performance of CdTe solar cells with antimony-containing RGO back contacts. The results indicate that, the introduction of extrinsic doping near the CdTe back surface serves to reduce the back contact depletion width and enhance the built-in potential to enable the tunnelling of majority carrier holes through the barrier, and the RGO is beneficial for the formation of Ohmic back contact on CdTe.